2013
DOI: 10.1017/jfm.2013.301
|View full text |Cite
|
Sign up to set email alerts
|

Flow physics and RANS modelling of oblique shock/turbulent boundary layer interaction

Abstract: Large-eddy simulation (LES) is utilized to investigate flow physics and lower-fidelity modelling assumptions in the simulation of an oblique shock impinging on a supersonic turbulent boundary layer (OSTBLI). A database of LES solutions is presented, covering a range of shock strengths and Reynolds numbers, that is utilized as a surrogate-truth model to explore three topics. First, detailed conservation budgets are extracted within the framework of parametric investigation to identify trends that might be used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
57
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(74 citation statements)
references
References 52 publications
17
57
0
Order By: Relevance
“…In particular, this link seems to have a nonlinear origin consistent with the results given by Sansica et al (2014). An interesting synthesis of these different scenarios is given by Morgan et al (2013).…”
Section: Discussionsupporting
confidence: 73%
“…In particular, this link seems to have a nonlinear origin consistent with the results given by Sansica et al (2014). An interesting synthesis of these different scenarios is given by Morgan et al (2013).…”
Section: Discussionsupporting
confidence: 73%
“…While not seen in the experiments (likely due to the uncertainty associated with the extrapolation procedure), we note that a very similar sudden decrease in C f at the the shock-induced separation was also observed in both the DNS by Pirozzoli and Bernardini [33] and the wall-resolved LES by Morganet al [34]. In addition, both these highly resolved studies showed similar dips in C f at the beginning and end of the low-friction plateau-region as seen in the present results.…”
Section: A Statistical Comparisonssupporting
confidence: 75%
“…Touber & Sandham (2009) were probably among the first to publish a successful comparison between their long-time (10 4 δ 0 U 0 ) narrow-domain LES results and experimental data with respect to the unsteady shock motion. Further LES studies for impinging SWBLI with a focus on low-frequency aspects of the interaction have been published thereafter (Pirozzoli et al 2010;Hadjadj 2012;Agostini et al 2012;Aubard et al 2013;Morgan et al 2013;Pasquariello et al 2014;Nichols et al 2016). All of these studies, however, predominantly focused on weak interactions (with respect to the absence of a distinct pressure plateau within the separated flow) and/or low Reynolds numbers being typically below Re δ0 ≈ 60 ⋅ 10 3 .…”
Section: Introductionmentioning
confidence: 99%